The Right of Navigation V. Freedom of Navigation: Balancing Rights and Obligation in Archipelagic Sea-Lane Passage - Enny Narwati; A Indah Camelia; Lina Hastuti (Jurnal Hukum, 2026)
This article examines three unresolved legal ambiguities within the archipelagic sea lanes passage (ASLP) regime under Part IV of the United Nations Convention on the Law of the Sea 1982 (UNCLOS): the permissible scope of an archipelagic state regulatory authority; the enforceability of Part XII UNCLOS environmental obligations without impeding navigation; and the legal consequences of deviation from designated sea lane routes. Employing doctrinal legal research through a treaty interpretation methodology derived from Articles 31–33 of the Vienna Convention on the Law of Treaties 1969 (VLCT) and Indonesia’s Archipelagic Sea Lanes (IASP) as operationalised ASLP case study. This article advances three original arguments: First, ASLP is conceptually grounded in right of Navigation (RoN) – a conditional, treaty-based entitlement – rather than in the customary-law derived Freedom of Navigation (FoN), a distinction carrying material consequences for coastal state regulatory competence. Second, UNCLOS Part XII environmental obligations function as lex generalis alongside the lex specialis of Part IV, permitting proportionate emergency environmental intervention without nullifying navigational rights. Third, unjustified departure from designated routes activates full scope of archipelagic supervisory authority, including the innocent passage framework. These findings contribute to the cooperative governance of strategically critical maritime corridors and inform undesignated ASLP regimes globally.